Adoption of Social Networking Sites among Pakistani University Students: A Case of Face-Book - Sabir, Raja Irfan; Ahmad, Wasim; Noor, Nabila; Rehman, Asad-ur- (Journal of Asian Business Strategy, 2013)
Since birth of Social Networking Sites (SNSs), these attracted millions of users from all around the world. The SNSs have changed the communication ways of people from more traditional to modern approaches. This study aims to examine diffusion and adoption of Facebook.com among Pakistani university students using Technology Acceptance Model (TAM) and Theory of Reasoned Action (TRA) with an extension of Theory of Planned Behavior (TPB). The study used stratified random & pre-tested questionnaire based on 5-point Likert scale to record answers. Structural Equation Modeling using AMOS Graphics 20.0, reliability statistics and descriptive statistics were used to illustrate & analyze collected data. The findings indicate surprising outcomes about no significant impact of perceived enjoyment, perceived ease of use, news, and attitude factor of TAM and TRA found on intention to use Facebook. Perceived usefulness & social norm proved to be the most important factors. With the help of these findings, marketers and advertisers can better develop their marketing strategies and advertising campaigns, e.g. especially viral marketing. The insufficient sample confined area and dependence of findings on prior tested theories of TAM impose limitations on the generalizability of findings